Bacterial Cell Enlargement Requires Control of Cell Wall Stiffness Mediated by Peptidoglycan Hydrolases - Richard Wheeler (American Society for Microbiology, 2015)
ABSTRACT Most bacterial cells are enclosed in a single macromolecule of the cell wall polymer, peptidoglycan, which is required for shape determination and maintenance of viability, while peptidoglycan biosynthesis is an important antibiotic target. It is hypothesized that cellular enlargement requires regional expansion of the cell wall through coordinated insertion and hydrolysis of peptidoglycan. Here, a group of (apparent glucosaminidase) peptidoglycan hydrolases are identified that are together required for cell enlargement and correct cellular morphology of Staphylococcus aureus, demonstrating the overall importance of this enzyme activity. These are Atl, SagA, ScaH, and SagB. The major advance here is the explanation of the observed morphological defects in terms of the mechanical and biochemical properties of peptidoglycan. It was shown that cells lacking groups of these hydrolases have increased surface stiffness and, in the absence of SagB, substantially increased glycan chain length. This indicates that, beyond their established roles (for example in cell separation), some hydrolases enable cellular enlargement by making peptidoglycan easier to stretch, providing the first direct evidence demonstrating that cellular enlargement occurs via modulation of the mechanical properties of peptidoglycan. IMPORTANCE Understanding bacterial growth and division is a fundamental problem, and knowledge in this area underlies the treatment of many infectious diseases. Almost all bacteria are surrounded by a macromolecule of peptidoglycan that encloses the cell and maintains shape, and bacterial cells must increase the size of this molecule in order to enlarge themselves. This requires not only the insertion of new peptidoglycan monomers, a process targeted by antibiotics, including penicillin, but also breakage of existing bonds, a potentially hazardous activity for the cell. Using Staphylococcus aureus, we have identified a set of enzymes that are critical for cellular enlargement. We show that these enzymes are required for normal growth and define the mechanism through which cellular enlargement is accomplished, i.e., by breaking bonds in the peptidoglycan, which reduces the stiffness of the cell wall, enabling it to stretch and expand, a process that is likely to be fundamental to many bacteria.